(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Cancer is indeed a group of illnesses, and each has its own range of symptoms, and each organ and system has its own list of conditions. Many cases of breast cancer may well be averted, with some estimates claiming that up to 30% of cancer deaths are connected to smoking and other lifestyle choices or food habits that could have been avoided by behavioral changes. Cancer therapy is a treatment of tumor in a patients through surgery, chemotherapy, or irradiation. Targeted therapies are also available for specific cancer types. A cancer sufferer may be subjected to a range of therapies, including those targeted at reducing cancer pain sensations. Nanotechnology has the ability to improve the selectivity or efficacy of physical, chemical, or biological methods to cancer cell killing while reducing nonmalignant cell damage. Nanomaterials are progressively being used to target tumor cells with high selectivity, both actively or passively. The primary goal of this study is to have a better understanding of cancer treatment and therapy.